Sustainability assessment of recycled aggregates concrete mixes containing industrial by-products. (September 2019) - Ahmed Shaikh, F.U.; Nath, P.; Hosan, A.; John, M.; Biswas, W.K.
Abstract: Virgin natural aggregates make up approximately 80–85% of the volume of concrete commonly used by Western Australian councils in their infrastructure. These councils generate a huge amount of construction and demolition (C&D) waste, most of which is sent to landfill. While C&D waste can potentially be used in pavements, only 22% of the total 1.5M tonnes of C&D waste generated in Western Australia (WA) each year is recycled. Experimental tests conducted in the Civil Engineering Laboratory of Curtin University have confirmed that concrete mixes utilizing recycled aggregates, fly ash (FA), and silica fume (SF) are structurally sound. The experimental results have shown that these new concrete formulations can potentially be considered for higher compressive strength applications. Concrete containing a maximum of 100% C&D waste from aggregate has been found to exceed the compressive strength (i.e. 40 MPa) required for most structural applications. Importantly, the potential use of this new concrete in WA residential flooring could divert significant amounts of C&D waste from landfill. Life cycle assessment of these concrete mixes suggested that the mixes using 50% natural aggregates, 50% recycled aggregates, and between 10% and 40% of by-products as cementitious materials have the highest reduction potential for global warming impact and embodied energy because of their higher compressive strength. Between 14 and 21% of cumulative energy consumption and 25–31% of global warming, impacts could be avoided with the use of 50 natural coarse aggregate (NA)+50100 recycled coarse aggregate (RA)+90 ordinary Portland cement (OPC)+10SF and 50NA+50RA+60OPC+30FA+10SF concrete formulations instead of 100NA (natural aggregate)+100OPC concrete to provide the same compressive strength. These two alternative mixes were found to reduce the cost by 7%–18%. The recycling of unused C&D wastes could also provide new employment opportunities and significant improvements in resources conservation, including land and biodiversity. Furthermore, between 90 and 280 GWh, energy can potentially be saved because of the replacement of energy-intensive natural aggregates with different mixes of recycled aggregate concrete.